2017
DOI: 10.1007/s10096-017-3111-8
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of microcephaly resulting from congenital infections: why is my baby’s head so small?

Abstract: The emergence of Zika-virus-associated congenital microcephaly has engendered renewed interest in the pathogenesis of microcephaly induced by infectious agents. Three of the original "TORCH" agents are associated with an appreciable incidence of congenital microcephaly: cytomegalovirus, rubella virus, and Toxoplasma gondii. The pathology of congenital microcephaly is characterized by neurotropic infectious agents that involve the fetal nervous system, leading to brain destruction with calcifications, microceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 180 publications
0
11
0
3
Order By: Relevance
“…Brain calcifications may be seen in other congenital infections, for example, cytomegalovirus and toxoplasmosis infection, but in these cases are predominantly periventricular [9,27]. This pattern of brain malformations in ZIKV is compatible with the fetal brain disruption sequence observed in congenital infections [28]. Experimental models showed that ZIKV targets human brain cells, reducing their viability and growth, suggesting that it abrogates neurogenesis during human brain development [29].…”
Section: Discussionmentioning
confidence: 89%
“…Brain calcifications may be seen in other congenital infections, for example, cytomegalovirus and toxoplasmosis infection, but in these cases are predominantly periventricular [9,27]. This pattern of brain malformations in ZIKV is compatible with the fetal brain disruption sequence observed in congenital infections [28]. Experimental models showed that ZIKV targets human brain cells, reducing their viability and growth, suggesting that it abrogates neurogenesis during human brain development [29].…”
Section: Discussionmentioning
confidence: 89%
“…The scale of publicity of the problem with the Zika virus (ZIKV) epidemic in South America, and especially its serious effects for pregnant women and their children, drew the attention of the general public to the relationship between infections with other pathogens, and the occurrence of malformations in the foetus which are just as serious as in the case of the Zika virus [1]. For example, microcephaly, which is mainly associated with Zika virus infection during pregnancy, can also be the result of infection with three other original 'TORCH' pathogens: cytomegalovirus (CMV), rubella virus (RBV) and Toxoplasma gondii [2]. Depending on the pathogen, the type of infection (primary, reactivation, reinfection), and pregnancy trimester in which infection occurs, the vertical transmission of the infectious agent from the mother to the developing foetus can have different effects -from complete lack of consistency to serious malformations and, in extreme cases, to pregnancy loss due to spontaneous abortion, foetal death or premature birth [3].…”
Section: Introductionmentioning
confidence: 99%
“…5 The majority of infected people remain asymptomatic or develop mild symptoms like fever, conjunctivitis, myalgia, and rash. 6,7 However, more severe complications such as Guillain-Barré syndrome in adults 8,9 and microcephaly and other congenital malformations in the developing fetus and newborns [10][11][12][13][14] have been associated with ZIKV infection and led to the declaration of ZIKV as a Public Health Emergency of International Concern by the World Health Organization (WHO) in 2016. 15 Its occasionally severe pathogenicity in combination with the detection of asymptomatic but viremic blood donors in French Polynesia, Martinique, Puerto Rico and the US [16][17][18][19][20][21][22] and three probable cases of ZIKV transfusion-transmission in Brazil 23,24 have made ZIKV a concern for blood safety.…”
mentioning
confidence: 99%
“…The majority of infected people remain asymptomatic or develop mild symptoms like fever, conjunctivitis, myalgia, and rash . However, more severe complications such as Guillain‐Barré syndrome in adults and microcephaly and other congenital malformations in the developing fetus and newborns have been associated with ZIKV infection and led to the declaration of ZIKV as a Public Health Emergency of International Concern by the World Health Organization (WHO) in 2016…”
mentioning
confidence: 99%